PTERIDOPHYTA DI KAWASAN AIR TERJUN SUHOM KECAMATAN LHOONG KABUPATEN ACEH BESAR - Wardiah Wardiah; Intan Sarina; Cut Nurmaliah; Hasanuddin hasanuddin (Biotik, 2019)
Fern is one of vegetation groups in the area of Suhom Waterfall, Lhoong District, Aceh Besar, Aceh, Indonesia. The study was aimed to determine the species of Pteridophyta scattered in the Suhom Waterfall Area, Lhoong District, Aceh Besar and their feasibility as a learning media of the Botany of Non-Vascular Plant course. The qualitative approach was used in this survey study. The research location was divided into three stations, Station I (the area above the waterfall), Station II (around the pool), and Station III (the river flow). Data were analyzed descriptively and the results showed that there were 33 species of Pteridophya that were classified into 4 Classis and 14 Familia. The Classis and Familia were Filicinae (Aspleniaceae, Anthyriaceae, Blechnaceae, Davalliaceae, Dropteridaceae, Glecheniaceae, Marceliaceae, Polypodiaceae, Pteridaceae, Schizaceae and Thelipteridaceae), Lycoopodiinae (Selaginellaeae), Lycoopodiinae (Selaginellaeae), and Psilotinae (Psilotaceae).